Redescription of Aposycorax chilensis (Tonnoir) (Diptera, Psychodidae, Sycoracinae) with the first identification of a blood meal host for the species - Curler, Gregory R.; Moulton, John K.; Madriz, R. Isai (Zootaxa, 2015)
Adults of Aposycorax chilensis were collected from several sites during fieldwork in Chilean Patagonia, December 2013. Specimens were swept or aspirated from roadside seeps and found in greatest numbers during the morning hours. DNA was extracted from a recently blood-fed female and was subjected to the polymerase chain reaction using vertebrate-specific 16S primers. An amplicon was obtained and the resulting sequence was found to have over 99% identity with two frogs in the genus Batrachyla, thus establishing this species’ preference for amphibian hosts. The diagnosis and description of adult A. chilensis are revised, including the first description of the complete male genital tract. Habitat characteristics for this species and rotation of the male genitalia are discussed.